Practical Values of Thesaurus of Modern Chinese in Nursing Scope Vocabulary - Wiratikusuma, Fransiska; Wiratikusuma, Yohana (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2022)
Abstract. The perspective formed by the mother tongue frequently influences the vocabulary used in speaking and writing while learning a new language. To make identifying and selecting the appropriate vocabulary according to the terminology commonly used by native speakers in the nursing field easier, Mandarin learners, notably those studying nursing, need vocabulary references that are organised systematically based on vocabulary domains. This study aims to serve as a resource for the processes in learning to increase overall proficiency in Mandarin for nursing. A Thesaurus of Modern Chinese (TMC) contains the lexical-semantic structure of Mandarin. Therefore, Chinese learners can learn the syntactic language that native Chinese speakers regularly use. This study examines the scope of vocabulary case studies in nursing from this thesaurus. The research strategy looks for relevant terminology in the nursing sector. This study also investigates the value of knowing Chinese to help nursing careers and the exposure to learning Mandarin in the nursing industry by related vocabulary. By selecting the nursing scope vocabulary from the thesaurus, This study can take more terms, particularly complex words, which are simple for native speakers but challenging for foreign learners.Keywords: A Thesaurus Of Modern Chinese; Mandarin Language Ability; Career Advancement; Nursing Expertise; Vocabulary